A Comprehensive Study of Orchid Seed Production Relative to Pollination Traits, Plant Density and Climate in an Urban Reserve in Western Australia - Mark C. Brundrett (Diversity, 2019)
The pollination of 20 common terrestrial orchids was studied in a 60-ha urban banksia and eucalypt dominated woodland in Western Australia. Five years of data (24,000 flowers, 6800 plants) measured fruit set relative to floral areas, capsule volumes, climate, phenology, pollination mechanisms, disturbance tolerance and demography. Pollination varied from 0−95% of flowers, floral displays from 90−3300 mm2 and capsules from 15−1300 mm3 per spike. Pollination traits strongly influenced outcomes, with self-pollination highest (59—95%), followed by sexually deceptive autumn or winter-flowering (18−39%), visual deception (0−48%) and sexually deceptive spring-flowering (13−16%). Pollination was limited by drought in autumn or spring and cool winter temperatures. Some orchids were resilient to drought and one formed seed after the leaves withered. Plant density had the greatest impact on fruit set for orchids forming large groups, especially for sexually deceptive pollination. Consequently, small group average (SGA) pollination was up to 4× greater than overall averages and peak seed production occurred in the best locations for genetic exchange and dispersal. SGA rates and seedpod volumes were strongly linked to clonality, but not to demographic trends. Resource competition limited flowering at higher plant densities and competition within spikes resulted in smaller, later-forming seedpods. Pollination data from co-occurring common orchids identified five evolutionary trade-offs linked to pollination, provided baseline data for rare species and revealed impacts of changing climate.